Love of Nature and Women in John Masefield's "Beauty” and Goran’s “Women and Beauty": A Comparative Study - Hasan, Mariwan; Mohammed , Saman (NOBEL: Journal of Literature and Language Teaching, 2021)
This research is a comparative study entitled Love of Nature and Women in John Masefield’s “Beauty” and Goran’s “Women and Beauty.” Textual and analytical approaches are used to analyze the poems to highlight the differences and similarities between the two poems. The analysis compares and contrasts both poems by each topic of discussion, including the theme and the rhyme pattern. This paper finds that although both Masefield and Goran come from different cultures and periods, the earlier from the romantic era while the latter is a modern poet, their poems agree in expressing the beauty of nature. However, the poems then state that the beauty of nature is nothing compared to the beauty of their beloved ones. The analysis also explores the different portrayals of nature that the poets depict and the rhyme pattern they prefer. This study then shows that the same issue can always come from works from a very different time and culture.